2022
DOI: 10.1155/2022/7177192
|View full text |Cite
|
Sign up to set email alerts
|

HSPA5 Could Be a Prognostic Biomarker Correlated with Immune Infiltration in Breast Cancer

Abstract: Background. Breast cancer (BC) is a frequent disease in females. The heat shock 70 kDa protein 5 (HSPA5) has recently been discovered to have an important function in tumor growth. However, the biological significance of HSPA5 in BC is unknown. Material and Method. Firstly, The Cancer Genome Atlas (TCGA) database was applied to analyze the expressions of HSPA5 in different cancer types, especially in BC. Then, the LinkedOmics database was used to screen genes coexpressed with HSPA5 in BC, presented by protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Leave-one-out cross validation and ROC analysis indicated that the gene feature had a moderate effect on predicting survival rate. Previous studies suggested that the three GRGs we found were all related to the occurrence and development of some cancers ( 29 - 31 ). For example, decreased expression of HSPA5 is associated with the deterioration of clinical pathological characteristics, shortened PFI, and increased immune infiltration of various immune cells, indicating that HSPA5 is a biomarker for the prognosis of THCA ( 32 ).…”
Section: Discussionsupporting
confidence: 53%
“…Leave-one-out cross validation and ROC analysis indicated that the gene feature had a moderate effect on predicting survival rate. Previous studies suggested that the three GRGs we found were all related to the occurrence and development of some cancers ( 29 - 31 ). For example, decreased expression of HSPA5 is associated with the deterioration of clinical pathological characteristics, shortened PFI, and increased immune infiltration of various immune cells, indicating that HSPA5 is a biomarker for the prognosis of THCA ( 32 ).…”
Section: Discussionsupporting
confidence: 53%
“…High expression of HSPA5 was found in lung cancer, gastric cancer, prostate cancer, CC and other tumor cells. As a cancer promoting factor, HSPA5 can reduce the lethal effect of cytotoxic T cells on tumor cells, protect tumor cells from the control of the body's immunity, and thus promote the occurrence and development of tumors [33] . This is also the case in our study, where high expression of HSPA5 in CC is associated with lower survival and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the database of The Cancer Genome Atlas (TCGA), the Tumor Immune Estimation Resource (TIMER) method, the Kaplan-Meier plotter, or Cox regression, Zhang et al. ( 17 ) concluded that HSPA5 is a marker for prognostics that correlates with immune infiltration of breast cancer. Dong et al.…”
Section: Hspa5 In Cancersmentioning
confidence: 99%